Avaliação do Programa Nacional de Vigilância, Prevenção e Controle das ISTs e do HIV/AIDS no uso da profilaxia pré-exposição ao HIV por pacientes do Hospital Universitário Walter Cantídio - Santos, Edelino Alves dos (2024)
The National Program for the Surveillance, Prevention, and Control of STIs and HIV/AIDS, which is the focus of this study, specifically regarding the implementation of the Pre-Exposure Prophylaxis (PrEP) program for Human Immunodeficiency Virus (HIV) at Walter Cantídio University Hospital (HUWC), has been a pioneer in the fight against Acquired Immunodeficiency Syndrome (AIDS) in Brazil since the 1980s. It serves as a critical intervention tool for controlling the disease nationwide. According to the most recent HIV/AIDS epidemiological report from the Brazilian Ministry of Health, a total of 1,088,536 AIDS cases were diagnosed between 1980 and June 2022, with an annual average of 36,400 new cases over the past five years and 40,880 new HIV infection cases reported in 2021 alone. The most recent epidemiological bulletin from the Ceará State Health Department reported a significant increase in HIV infection cases, rising from 690 cases in 2013 to 2,018 cases in 2021. From 2013 to 2022, most AIDS cases resulted from exposure among individuals engaging in exclusively same-sex practices, while one-third of all diagnosed HIV cases involved bisexual and homosexual individuals. These trends highlight the significant role of key populations in the dynamics of the AIDS epidemic in Ceará. Consequently, the epidemic continues to affect the most vulnerable segments of the population disproportionately. This study aimed to evaluate the National Program for the Surveillance, Prevention, and Control of STIs and HIV/AIDS in the context of the implementation of the PrEP program at HUWC. The theoretical framework employed analytical categories such as healthcare access, equity, vulnerability, stigma, prejudice, and discrimination. This research is classified as a descriptive case study, with a qualitative approach and quantitative contributions, conducted from the perspective of in-depth evaluation. The investigation took place at HUWC and included all users enrolled in the PrEP program and all professionals from diverse disciplines involved in its implementation. Data were collected using a triangulated approach, including bibliographic, field, and document research, as well as semi-structured interviews with the multidisciplinary healthcare team and program users. The analysis included a statistical description and thematic analysis. The results are presented using tables, graphs, and narrative descriptions of participants' statements and significant observed events. Findings were discussed in light of current literature. Ethical guidelines outlined in Resolution No. 466/2012 of the Brazilian National Health Council were adhered to, ensuring no harm to participants, and the study was approved by the HUWC Research Ethics Committee under Opinion No. 6.570.956. The results showed that the HUWC PrEP program primarily serves cisgender men, gay individuals, people of mixed race, those with complete or incomplete higher education, and residents of Fortaleza. However, user retention in the program was found to be low, with a high dropout rate concentrated mainly in the initial months of follow-up. Interviews with professionals and users highlighted barriers and challenges to accessing and staying in the program, including issues related to service infrastructure, care organization, communication, and a lack of awareness about PrEP. In conclusion, the objectives of the National STI/HIV/AIDS Program are not fully achieved in the local context of PrEP implementation at HUWC. The program requires restructuring to optimize its impact on HIV/AIDS prevention.